TINJAUAN PENEGAKAN HUKUM PASAL 88 UNDANG-UNDANG NO. 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK SEBAGAI STRATEGI ALTERNATIF DALAM PERKARA TINDAK PIDANA PERDAGANGAN ORANG: STUDI POLDA GORONTALO - Salsabila Malitza Laliyo; Suwitno Yutye Imran; Julius T. Mandjo (CV Widina Media Utama, 2026)
Human trafficking crimes targeting children are complex offenses that violate human rights; however, the process of proving the elements of these offenses in law enforcement practice often faces significant practical challenges. This study aims to examine the law enforcement mechanisms, the rationale for its application, as well as the obstacles and effectiveness of Article 88 of Law No. 35 of 2014 on Child Protection as an alternative strategy in handling TPPO cases at the Gorontalo Regional Police. The research method employed was a normative-empirical legal approach using both a statutory approach and a factual approach, through the collection of primary data from interviews at Sub-Directorate IV Renakta of the Gorontalo Regional Police, as well as secondary data in the form of literature reviews and court decision documents. The results of the study indicate that investigators at Sub-Directorate IV Renakta of the Gorontalo Regional Police apply Article 88 of the Child Protection Law as an alternative strategy through the construction of layered presumptions to overcome the difficulty of proving the rigid transactional elements in the Trafficking in Persons Law, as implemented in Gorontalo District Court Decision No. 71/Pid.Sus/2024/PN Gto. Despite facing multidimensional challenges—such as limited evidence, a scarcity of eyewitnesses, and cultural factors within the community—this provision has proven effective as a legal safety net to prevent impunity for perpetrators. The application of Article 88 of the Child Protection Law as an alternative strategy at the Gorontalo Regional Police Headquarters has strong legal relevance based on the theory of concurrence to ensure substantive justice and maximum protection for child victims of exploitation. ABSTRAKTindak pidana perdagangan orang (TPPO) yang menyasar anak merupakan kejahatan kompleks yang merampas hak asasi manusia, namun proses pembuktian unsur-unsur pasalnya dalam praktik penegakan hukum sering kali menghadapi kendala materiil yang berat. Penelitian ini bertujuan untuk mengkaji mekanisme penegakan hukum, alasan penerapan, serta kendala dan efektivitas Pasal 88 Undang-Undang Nomor 35 Tahun 2014 tentang Perlindungan Anak sebagai strategi alternatif dalam penanganan perkara TPPO di Kepolisian Daerah Gorontalo. Metode penelitian yang digunakan adalah yuridis normatif-empiris dengan pendekatan perundang-undangan (statute approach) dan pendekatan fakta (fact approach), melalui pengumpulan data primer hasil wawancara di Subdit IV Renakta Polda Gorontalo serta data sekunder berupa studi kepustakaan dan dokumen putusan pengadilan. Hasil penelitian menunjukkan bahwa penyidik Subdit IV Renakta Polda Gorontalo menerapkan Pasal 88 UU Perlindungan Anak sebagai strategi alternatif melalui konstruksi persangkaan berlapis guna mengatasi kesulitan pembuktian unsur transaksional yang kaku pada UU TPPO, seperti yang diimplementasikan pada Putusan PN Gorontalo Nomor 71/Pid.Sus/2024/PN Gto. Meskipun dihadapkan pada kendala multidimensional seperti keterbatasan alat bukti, minimnya saksi mata, dan faktor budaya masyarakat, pasal ini terbukti efektif sebagai legal safety net untuk mencegah impunitas pelaku. Penerapan Pasal 88 UU Perlindungan Anak sebagai strategi alternatif di Polda Gorontalo memiliki relevansi yuridis yang kuat berdasarkan teori konkurrensi untuk menghadirkan keadilan substantif dan perlindungan maksimal bagi anak korban eksploitasi.